Assessing the Legal Implications of Alleged Fuel Blending on Indonesia's Compliance with the Paris Agreement - Silalahi, Dafanail Yonathan; Rahan Mentari Wicak; Reva Putri Saffanah; Alma Shofi Thufaila (Faculty of Law Universitas Sebelas Maret, 2024)
This study examines the impact of PT Pertamina Niaga's alleged fuel mixing case on Indonesia's commitment to the Paris Agreement. The research analyzes how mixing higher octane fuels (RON 92) with lower octane fuels affects carbon emissions and contributes to environmental degradation. Through case study methodology comparing Indonesia's policies with successful implementations in Canada and the Philippines, the research reveals significant challenges in Indonesia's emission reduction efforts. The findings demonstrate that Indonesia faces obstacles in meeting its Nationally Determined Contribution targets due to heavy reliance on fossil fuels, inadequate investment in renewable energy infrastructure, and weak regulatory enforcement. The study highlights the ineffectiveness of the Paris Agreement's enforcement mechanisms and proposes solutions including expanding green finance policies, transitioning to clean energy, strengthening compliance mechanisms, and implementing carbon pricing strategies similar to the Carbon Border Adjustment Mechanism. This research contributes to understanding the intersection between corporate practices, environmental regulations, and international climate commitments in developing nations.